A FRAMEWORK FOR INTEGRATING ESG CRITERIA INTO STRATEGIC HUMAN RESOURCE PLANNING - M Saiful Rizal; Handoko Teguh (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The global shift from shareholder primacy to stakeholder capitalism has put criteriaEnvironmental, Social, and Governance(ESG) as the gold standard for corporate success. However, there is a significant gap between high-level ESG commitments and tactical implementation in Human Resource Management (HRM). This study develops a conceptual framework for integrating ESG criteria into strategic HR planning through a systematic narrative review of the literature from 2016–2026. The study reveals that the "Environmental" pillar is operationalized through green recruitment and sustainability competencies, while the "Social" pillar emphasizesDiversity, Equity, and Inclusion(DEI) and employee well-being. Crucially, the often-overlooked "Governance" pillar in HRM discourse is integrated through ethical leadership, remuneration transparency, and meritocracy-based succession planning. This integration transforms the role ofHR Business Partner into a Sustainability Partner, redefined through the lensResource-Based View(RBV) and Institutional Theory. This framework provides a strategic roadmap for organizations to increase long-term resilience and legitimacy in a competitive talent market.